Exacerbated conceptus signaling does not favor establishment of pregnancy in beef cattle - Martins, T. (J Anim Sci Biotechnol, 2018)
BACKGROUND: Insufficient production of anti-luteolytic signals by the pre-attachment embryo is considered a major cause of pregnancy failure in cattle. We tested the hypothesis that transfer of multiple blastocysts (n = 5/recipient) and progesterone (P4) supplementation amplify anti-luteolytic signaling and reduce embryonic losses in beef cattle. Cows detected in estrus (D0; n = 104) were assigned randomly to receive 150 mg of injectable long-acting P4 (iP4) or vehicle (non-iP4) on D4 and transcervical transfer of none or five, grade 1, not-frozen, in vitro-produced blastocysts, on D7. Luteal development and time of structural luteolysis were monitored by ultrasonography. Plasma P4 concentrations were determined on D4, D5 and D7, and daily between D14 and D20. Conceptus signaling was monitored by transcript abundance of interferon-stimulated gene 15 (ISG15) in peripheral blood mononuclear cells isolated on D14, D16, D18 and D20. Early embryonic mortality (EEM) was defined as the absence of ISG15 mRNA upregulation over time and/or luteal regression up to D20. Late embryonic mortality (LEM) was defined as the absence of a conceptus with a heartbeat on pregnancy diagnosis at D30 (PD30) after observing upregulation of ISG15 mRNA and extension of luteal lifespan. Pregnant cows presented conceptuses with heartbeat at PD30. RESULTS: On D5, iP4-treated cows had P4 concentrations 2.07-fold greater than non-iP4 treated (P < 0.001). On D7, P4 concentrations were similar. Pregnant and LEM animals showed a progressive increase in the abundance of ISG15 from D14 to D20. iP4-treated cows detected pregnant at PD30 had 1.53-fold greater abundance of ISG15 mRNA between D14 and D20 than non-iP4 treated cows (P = 0.05). iP4 doubled the frequency of EEM while it did not affect LEM. At PD30, embryonic survival was 37.0% vs. 55.6% for iP4-treated vs. control cows. Majority of pregnant cows (71%) presented only a single viable embryo. CONCLUSIONS: A substantial proportion of cows had EEM (31%) and LEM (20%) even after transferring multiple blastocysts. This argues that mortality was due to poor uterine receptivity that could not be reversed by supplemental P4 or overcome by transferring multiple blastocysts. Further, a given uterine environment was not necessarily adequate to all embryos.